Gambaran Pengelolaan Limbah Medis Padat pada Pusat Kesehatan Masyarakat di Kabupaten Alor - Jackson Ronaldo Adang; Doke, Soni; Sahdan, Mustakim (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Puskesmas, as one of the health care facilities, has an obligation to maintain the environment and the health of the surrounding community, and is fully responsible for the waste produced. Cases of accumulation of medical waste in health care facilities are caused by the lack of a medical waste treatment system in health care facilities in each region. This study aims to determine the description of solid medical waste management at Kokar Health Center, Alor Kecil Health Center, and Moru Health Center in Alor Regency. This research type is descriptive qualitative using a case study design, and data collection is done by in-depth interviews with 17 informants. The results of this study are the sorting and collection stages of solid medical waste have been carried out properly, the transportation stage at Puskesmas Kokar and Puskesmas Alor Kecil is carried out using a trolley in good condition while Puskesmas Moru is still done manually, the temporary storage stage is not carried out in accordance with related regulations where the health center does not have a special place, the destruction and final disposal stage is carried out by capurization and incineration.